2021
DOI: 10.1186/s12935-021-02392-y
|View full text |Cite
|
Sign up to set email alerts
|

CircSEC24A upregulates TGFBR2 expression to accelerate pancreatic cancer proliferation and migration via sponging to miR-606

Abstract: Background Circular RNA (circRNA), producing by special selective splicing, was widely expressed in the cytoplasm of eukaryotic cells as a newly non-coding RNAs. It played different roles in a variety of diseases including cancer and performed different functions. Nonetheless, reports on the specific function of circRNA in pancreatic cancer (PC) were still rarely so far. In particular, the role of circSEC24A in PC remains unclear. Methods Real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As a consequence, we used the Targetscan database to discover putative miR-1179 target genes. Although many candidate genes emerged, TGFBR2, a predicted target, stood out and was chosen for further analysis, based on previous reports showing that TGFBR2 overexpression increases PC cell proliferation, migration, invasion, and EMT 11 , 12 . Using the UALCAN ( Figure 6a ) and GEPIA databases ( Figure 6b ), we showed that in TCGA PC samples, TGFBR2 levels were increased in PC tissues compared to normal tissues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, we used the Targetscan database to discover putative miR-1179 target genes. Although many candidate genes emerged, TGFBR2, a predicted target, stood out and was chosen for further analysis, based on previous reports showing that TGFBR2 overexpression increases PC cell proliferation, migration, invasion, and EMT 11 , 12 . Using the UALCAN ( Figure 6a ) and GEPIA databases ( Figure 6b ), we showed that in TCGA PC samples, TGFBR2 levels were increased in PC tissues compared to normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…When TGFBR2 expression was restored in miR-204-overexpressing gastric cancer cells, they regained resistance to 5-FU treatment 29 . Although previous reports showed that TGFBR2 functioned as a key oncogene to increase PC cell proliferation, migration, invasion, and EMT 11 , 12 , the roles of TGFBR2 in gemcitabine sensitivity in PC are still unknown. In the current work, we reported that TGFBR2 overexpression dramatically induced proliferation, migration, invasion, and gemcitabine resistance in PC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It decreased cell proliferation, migration, and invasion, making gemcitabine more effective as shown in Fig. 2 [ 76 ]. In the complex world of gene regulation, circular RNAs (circRNAs) like circEIF3I are crucial.…”
Section: Functional Implications Of Lncrna Through Hedgehog Signaling...mentioning
confidence: 99%
“…More importantly, alterations affecting circRNA expression have been reported to be linked to EMT to modulate tumor metastatic behavior [ 20 , 21 ]. circSEC24A is a newfound circRNA that has been reported to accelerate tumor progress in squamous cell carcinoma [ 22 ] and pancreatic cancer [ 23 ]. However, the function of circSEC24A in HCC is indistinct.…”
Section: Introductionmentioning
confidence: 99%